2011
DOI: 10.1371/currents.rrn1237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data and ploidal levels indicate several putative allopolyploidization events in the genus Potentilla (Rosaceae)

Abstract: Several naturally occurring hybrids in Potentilla (Rosaceae) have been reported, but no molecular evidence has so far been available to test these hypotheses of hybridization. We have compared a nuclear and a chloroplast gene tree to identify topological incongruences that may indicate hybridization events in the genus. Furthermore, the monophyly and phylogenetic position of the proposed segregated genera Argentina, Ivesia and Horkelia have been tested. The systematic signal from the two morphological characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
71
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 53 publications
14
71
1
Order By: Relevance
“…It is nested within Potentilla L. (cinquefoil) in the Rosaceae – a cosmopolitan family of large ecological and economic importance, which includes many edible fruits (apples, plums, cherries, pears, strawberries, almonds) as well as ornamentals (roses, firethorns, hawthorns). As currently circumscribed (Figures 1 and S1; [8][9], [11][12]), the ivesioid clade includes more than 50 species classified in three genera: Ivesia , Horkelia and Horkeliella [10], [13][14]. Common to many of them is that they grow under extremely dry conditions and have developed means to avoid drought (petrophily on protected rock faces, tolerance of alkalinity) or minimize water loss (increased pubescence, numerous minute leaflet segments in a tightly overlapping arrangement).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It is nested within Potentilla L. (cinquefoil) in the Rosaceae – a cosmopolitan family of large ecological and economic importance, which includes many edible fruits (apples, plums, cherries, pears, strawberries, almonds) as well as ornamentals (roses, firethorns, hawthorns). As currently circumscribed (Figures 1 and S1; [8][9], [11][12]), the ivesioid clade includes more than 50 species classified in three genera: Ivesia , Horkelia and Horkeliella [10], [13][14]. Common to many of them is that they grow under extremely dry conditions and have developed means to avoid drought (petrophily on protected rock faces, tolerance of alkalinity) or minimize water loss (increased pubescence, numerous minute leaflet segments in a tightly overlapping arrangement).…”
Section: Introductionmentioning
confidence: 90%
“…The ‘ivesioids’ are a well-supported plant clade [8][9] confined to western North America [10]. It is nested within Potentilla L. (cinquefoil) in the Rosaceae – a cosmopolitan family of large ecological and economic importance, which includes many edible fruits (apples, plums, cherries, pears, strawberries, almonds) as well as ornamentals (roses, firethorns, hawthorns).…”
Section: Introductionmentioning
confidence: 99%
“…Some other phylogenetic studies puplished in between of Potter et al (2007) and Faghir et al (2014) also confirmed monophyly of Potentilla and division of Potentilleae onto two subtribes (e. g., Dobeš, Paule, 2010;Töpel et al, 2011).…”
Section: Introductionmentioning
confidence: 60%
“…However, it is reasonable to speculate that the C. heptadactylus chromosome may be related to the C. myriocarpus (Ames 23540) and C. africanus (PI 542126 and PI 542127) chromosomes that have rch type III. Dioecy and polyploidy associations have been reported, for example, in the Lycium genus Venable, 2000, 2002;Yeung et al, 2005], the Potentilla genus [Cobon and Matfield, 1976;Holm and Ghatnekar, 1996;Töpel et al, 2011], and the Rubus genus [Sutherland, 2005]. The transition from monoecious diploids to dioecious polyploids by whole-genome duplication through conjunction with hybridization or by the generation of allo-or autopolyploids have been suggested as possible causes of loss-of-function phenotypes.…”
Section: Discussionmentioning
confidence: 99%